Absorption spectra of ammonia near 1 μm. (December 2017) - Barton, Emma J.; Polyansky, Oleg L.; Yurchenko, Sergei.N.; Tennyson, Jonathan; Civiš, S.; Ferus, M.; Hargreaves, R.; Ovsyannikov, R.I.; Kyuberis, A.A.; Zobov, N.F.; Béguier, S.; Campargue, A.
Abstract: An ammonia absorption spectrum recorded at room temperature in the region 8800–10, 400 cm −1 is analysed using a variational line list, BYTe, and ground state energies determined using the MARVEL procedure. BYTe is used as a starting point to initialise assignments by combination differences and the method of branches. Assignments are presented for the region 9400–9850 cm −1 . 642 lines are assigned to 6 previously unobserved vibrational bands, ( 2 v 1 + 2 v 4 2 ) ±, ( 2 v 1 + v 3 1 ) ± and ( v 1 + v 3 1 + 2 v 4 2 ) ±, leading to 428 new energy levels with 208 confirmed by combination differences. A recently calculated purely ab initio NH3 PES is also used to calculate rovibrational energy levels. Comparison with assigned levels shows better agreement between observed and calculated levels than for BYTe for higher vibrational bands. Abstract : Graphical abstract: fx1